Towards the Conflict and Compatibility of the Contemporary Economy with Nature - Pechočiaková Svitačová, Eva (Studia Ecologiae et Bioethicae, 2023)
The subject of interest is the constant deepening of the old conflict between culture and nature, and thus also the conflict with nature and the economy, which J. Šmajs considers to be a subsystem of culture. The conflict between nature and culture is considered to be the main cause of the global ecological crisis, which is a crisis of coexistence between humans and nature. Attention is drawn to the predatory economy, which Šmajs considers to be one of the causes of this conflict and which greatly influences the shape of contemporary culture. The main aim of the paper is to find ways in which this conflict, which has acquired a global dimension, can be mitigated and to advocate for the synergy or compatibility of the economy as well as the whole culture with nature. The solution is to move away from anthropocentrism, to reorient values in society based on a proper understanding of the phenomena of nature, culture and economy. Along with this, it is important to raise environmental awareness among economic actors, but practically among all people. We consider that to be an important step towards mitigating the above-mentioned conflict and towards the development of a sustainable economy and society.